People's Sovereignty and Constitutional Amendments: Reflections on Changes in Indonesia's Constitutional System - Rusman Rusman; Faisal Santiago; Tina Amelia (Siber Nusantara Research, 2026)
This paper examines how the principle of people's sovereignty is reflected through a series of amendments to the 1945 Constitution as well as its implications for the Indonesian constitutional system. With a normative-analytical approach, this paper examines the substance of key articles before and after amendments, examines constitutional political debates, and compares with the experiences of other countries. The results of the analysis show that the amendments have strengthened the mechanisms of people's participation, through representative institutions and decentralized mechanisms, but there are still challenges in the implementation of social control and the strengthening of checks and balances. Policy recommendations are directed at expanding participatory democratic instruments and strengthening independent oversight institutions.